Multidimensi pada Data Warehouse dengan Menggunakan Rumus Kombinasi - Spits Warnars Harco Leslie Hendric (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
Multidimensional in data warehouse is a compulsion and become the most important for information delivery, without multidimensional data warehouse is incomplete. Multidimensional give the able to analyze business measurement in many different ways. Multidimensional is also synonymous with online analytical processing (OLAP).Keywords: multidimensional, data warehouse, OLAP